Karakteristik Fisik dan Aktivitas Antioksidan dalam Pengembangan Nori dari Daun Mangrove Jeruju (Acanthus ilicifolius L.) - Sulfiana,; Hardianti A, Fatimah; Tanasali, Fadalia; Ghela, Maria Marselina; Kelibay, Amirula; Muslimin, Istyqamah (Journal Galung Tropika, 2025)
Indonesia has great potential in terms of mangrove ecosystems, with around 22.8% of the world's mangrove cover located in this country. One type of mangrove that is interesting to develop is Acanthus ilicifolius L. (jeruju), which contains useful secondary metabolites, such as alkaloids, flavonoids and saponins. This research aims to explore the potential of jeruju mangrove leaves as raw material for nori, a functional food rich in antioxidants. This research method includes making nori from jeruju mangrove leaves with variations in leaf concentration (P1: 25 g, P2: 50 g, P3: 75 g), and organoleptic analysis, as well as antioxidant activity. This research used laboratory experimental methods, using a Completely Randomized Design (CRD) with 3 treatments and 3 replications. The results showed that the nori produced had a blackish green color with a texture that varied according to the concentration of jeruju mangrove leaves. Organoleptic tests showed favorable results for panelists in the parameters of appearance, aroma, taste and texture, although there were significant differences in appearance. The results of the antioxidant activity test using the DPPH method showed that nori treated with P3 (75 g) had a lower IC50 value, indicating better antioxidant activity compared to other treatments. Based on nutritional content analysis, nori jeruju has competitive levels of protein, fat, fiber and carbohydrates, making it a functional food product with potential for further development.